Clinical effectiveness, cost-effectiveness and acceptability of community-based management of chronic hepatitis C: a mixed methods systematic review protocol. (April 2017) - Pourmarzi, Davoud; Hall, Lisa; Rahman, Tony; Lim, David; FitzGerald, Gerard
Abstract : Review question/objective: The current mixed methods review aims to develop an aggregated synthesis of quantitative, qualitative and economic systematic evidence on chronic hepatitis C virus (HCV) infection management intervention delivered in community settings so as to gain an increased understanding of the clinical effectiveness, cost-effectiveness and acceptability of community-based chronic HCV management. This review will contribute to the development of a community-based chronic HCV intervention and inform clinical practice and policy discussion. The overarching question is: What is the clinical effectiveness, cost-effectiveness and acceptability of community-based programs for chronic HCV management? The sub-questions to be addressed in the review are: What is the clinical effectiveness (proportion of antiviral treatment completion and sustained virologic response) of the community-based chronic HCV management programs? What is the acceptability (treatment uptake, adherence, engagement and satisfaction) of community-based chronic HCV management programs from the perspective of involved patients? How are the models funded and are they cost-effective? What are the organizational and operational elements of the models of community-based chronic HCV management?